Performance Evaluation of Wastewater Concentration Device: Analysis of Recovery Rate for Implementing SARS-coV-2 Wastewater-based Epidemiology - Brigita Dejus; Roberts Ozols; Martins Strods; Juris Laicans; Anna Zajakina; Ance Roga; Davids Fridmanis; Talis Juhna (Chemical Engineering Transactions, 2023)
To successfully implement wastewater-based epidemiology (WBE), a rapid, cost-effective, and sensitive method of concentrating SARS-CoV-2 virus RNA in wastewater is necessary. This study aimed to design a wastewater concentration device with an ultrafiltration membrane system and evaluate its performance by comparing its recovery rate (%) of virus RNA to the polyethylene glycol precipitation method. The results showed that there was no significant difference (p > 0.05) between the two methods, with recovery rates ranging between 80 – 85 %. This suggests that an ultrafiltration membrane system is a viable option for targeting COVID-19 in wastewater, as it can save time, and energy and reduce costs, making it suitable for the implementation of WBE.